RNF12 Promotes Glioblastoma Malignant Proliferation via Destructing RB1 and Regulating MAPK Pathway. (1st December 2021) - Sun, Eryi; Zhang, Ping
Abstract : Background . RNF12 has been linked to a variety of biological activities, including the control of the MDM2/P53 pathway, although its additional functions remain unclear. RNF12 was discovered to be a new ubiquitin ligase (E3) for RB1, amongst the most frequently repressed proteins in cancer of human. Method . Cell Counting Kit-8 was used to detect the cell proliferation; coimmunoprecipitation was used to determine that RNF12 interacts with RB1. Xenograft studies were used to verify the results. Result . In vivo and in vitro RNF12 interacts with RB1 regardless of E3 ligase activity. The ubiquitination of RB1 by RNF12 had an effect on its stability. RNF12 inhibits the RB1 protein and stimulates the MAPK pathway, promoting the growth of GBMs. Conclusion . Our findings show that RNF12 may operate as a tumour promoter by modulating the cancerous proliferation of glioblastoma by controlling the activity of a new RNF12/RB1/MAPK pathway regulatory axis and that this regulatory axis might be a valuable diagnostic focus in glioblastoma.